2018
DOI: 10.1177/1362361318815252
|View full text |Cite
|
Sign up to set email alerts
|

Effects of familiarization on odor hedonic responses and food choices in children with autism spectrum disorders

Abstract: This study assessed whether olfactory familiarization can render food odors more pleasant, and consequently food more attractive, to children with autism spectrum disorder. Participants were first presented with a series of food odors (session 1). Then, they were familiarized on four occasions (time window: 5 weeks) with one of the two most neutral odors (the other neutral odor was used as control) (session 2). In session 3, participants smelled the entire series of odors again. Both verbal and facial response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…It appears that both models are highly similar. The positive correlations between F and V for pleasant odors [12,[51][52][53][67][68][69][70][71][72][73], and between F and I [52,70], and between I and A [12,14,56,57] that have been reported in the literature, also emerge in both networks. Other known relations, such as the negative correlations between BV and T [86,147,148], and between I and V [55], also consistently emerge in both models.…”
Section: Discussionsupporting
confidence: 56%
“…It appears that both models are highly similar. The positive correlations between F and V for pleasant odors [12,[51][52][53][67][68][69][70][71][72][73], and between F and I [52,70], and between I and A [12,14,56,57] that have been reported in the literature, also emerge in both networks. Other known relations, such as the negative correlations between BV and T [86,147,148], and between I and V [55], also consistently emerge in both models.…”
Section: Discussionsupporting
confidence: 56%
“…Our results provide a new insight into the relationships between autistic traits, odor identification ability and olfactory trait hedonic capacity. Some studies have found that children with clinical and subclinical autistic traits as well as poor olfactory function showed more food neophobia behaviors (Luisier et al, 2015; Luisier, Petitpierre, Clerc Berod, Garcia‐Burgos, & Bensafi, 2019; Stafford et al, 2017; Wallace, Llewellyn, Fildes, & Ronald, 2018), which reduced the quality of life. Moreover, Qiu et al (2022) also found children with high autistic traits showed poor olfactory trait hedonic capacity, which may reduce the enjoyment of food and higher levels of food fussiness.…”
Section: Discussionmentioning
confidence: 99%
“…Digital game features could thus familiarize children to new food smells, increasing their familiarity without pressure of eating unwanted foods. As familiarity is strongly associated with liking and acceptance, this feature might reduce picky and fussy eating and reduce the risk for long-lasting food aversions (Luisier et al., 2019). Third, Exerscent enables new means of skills acquisition by food, drink, and fragrance professionals who may use Exerscent to cultivate both sensory and cognitive olfactory advantages (Croijmans et al., 2020).…”
Section: Discussionmentioning
confidence: 99%